Cloud computing adoption among state universities and colleges in the Philippines: Issues and challenges - Catherine R. Alimboyong; Mardie E. Bucjan (International Journal of Evaluation and Research in Education (IJERE), 2021)
The emergence of cloud computing (CC) adoption in higher education institutions (HEIs) is considered widespread today. Its growth comes with tremendous benefits and potential risks as well. This paper endeavors to investigate some issues and challenges that influence the adoption of cloud computing among state universities and colleges (SUCs) in the Philippines. A qualitative design was used in the study as it employed multiple case studies approach. Based on the results, this paper establishes two strong factors such as slow internet connection and lack of understanding or awareness of cloud computing. The findings revealed the impact of cloud computing to SUCs is found beneficial to the educational system amidst the global pandemic. Professors can easily upload lessons and teaching materials while students can easily access the materials online, though the challenge lies in the connectivity of internet in the country. Administrators can easily collaborate with the entire academic community and even to its stakeholder’s potential for collaboration even if not in face to face. It is a perfect avenue to be productive and efficient which allows all processes be made possible to all members of the entire academic community, may it be students, professors, staff and even other stakeholders.